Pediatric severe factor XI deficiency: A multicenter study. Issue 3 (26th December 2021) - Barg, Assaf Arie; Levy‐Mendelovich, Sarina; Budnik, Ivan; Mandel‐Shorer, Noa; Dardik, Rima; Avishai, Einat; Brutman‐Barazani, Tami; Ifrah, Aviya Dvir; Oren‐Malek, Liat; Yacobovich, Joanne; Gilad, Oded; Nakav, Sigal; et al.
Abstract: Background: Factor XI (FXI) deficiency is a rare autosomal recessive bleeding disorder. Only scarce publications address its clinical features in children. The increased prevalence of FXI deficiency in Israel enabled data collection for this large multicenter cohort study. Objective: Some hemostatic challenges may be unique or more common in children, such as bleeding in the neonatal period or trauma‐related injury. The current study was designed to explore the potential impact of these differences in children with severe FXI deficiency. Methods: Medical files of all children with FXI level under 15% followed at five tertiary centers were evaluated. The retrieved data comprised demographic and clinical characteristics, including bleeding episodes, surgical interventions, treatment strategies, as well as laboratory features. Results: Sixty children, whose median age at diagnosis was 4.2 years and their median FXI level was 4%, were included. Three children experienced triggered intracranial hemorrhage (ICH) and two children had major bleeds. No bleeding complications occurred in surgeries in which hemostatic treatment consisting mostly of tranexamic acid or fresh frozen plasma was applied ( n = 45). In contrast, excessive bleeding was noted in 25% of surgical procedures performed without hemostatic preparation ( p = .002). Conclusion: This study's findings confirm the generally favorable outcome of this rare bleeding disorder, with no spontaneous bleeds or cases of perinatal ICH. Nonetheless, proper diagnosis and adequate hemostasis in the surgical setting are imperative. Unlike previous studies in adults, our pediatric study suggests an association between the severity of FXI deficiency and bleeding tendency.